Poor sleep quality`s association with soccer injuries: Preliminary data - Silva, A.; Narciso, F. V.; Soalheiro, I.; Viegas, F.; Freitas, L. S. N.; Lima, A.; Leite, B. A.; Aleixo, H. C.; Duffield, R.; de Mello, M. T. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To investigate the relationship between sleep quality and quantity and injuries in elite soccer players and to compare sleep-wake variables and injury characteristics. Methods: The current investigation was a prospective cohort study of 23 elite male soccer players competing for 2 teams over 6 mo in the highest-level Brazilian competition. The players` sleep behavior was monitored for 10 d in the preseason using self-reporting sleep diaries and wrist activity monitors to determine sleep duration and quality. Furthermore, injuries were recorded by the respective club`s medical teams into a specific database. Details of injuries recorded included the type, location, and severity of each injury. The results were expressed as descriptive statistics, and the significance level was set at 5%. The Mann-Whitney U test was performed to compare the sleep variables between groups. Spearman correlation coefficient and linear-regression analysis were used. Results: The results indicated a moderate negative correlation between sleep efficiency and particular injury characteristics, including absence time, injury severity, and amount of injuries. The linear-regression analysis indicated that 44% of the total variance in the number of injuries can be explained by sleep efficiency, 24% of the total variance in the absence time after injury (days) can be explained by sleep efficiency, and 47% of the total variance in the injury severity can be explained by sleep efficiency. Conclusions: Soccer players who exhibit lower sleep quality or nonrestorative sleep show associations with increased number and severity of musculoskeletal injuries.